Pendampingan Ibu-Ibu dalam Kegiatan Rutin Yasinan dan Tahlilan Untuk Menumbuhkan Budaya Kerukunan - Dinda Masitoh Alvauziah; Haniatul Mukaromah (Social Science Academic, 2025)
This mentoring aims to strengthen the role of the mothers' routine Yasinan and Tahlilan activities in fostering a culture of community harmony in Dukuh Dayakan, Wagir Lor Village, Ngebel District. This activity is carried out using the Asset Based Community Development (ABCD) approach, which emphasizes the utilization of local assets, both material and non-material, based on the principle of Positive Deviance. The subjects of the mentoring are the local community, particularly the group of women who regularly hold Yasinan and Tahlilan ceremonies. The techniques used include observation and documentation, with the researcher's direct involvement in activities ranging from preparation, reading Yasin and tahlil, communal prayer, to social interaction after the event. The results of the mentoring show that Yasinan and Tahlilan not only serve as ritual worship but also as a social space that strengthens relationships, solidifies solidarity, and fosters care among residents. This tradition plays an important role in maintaining a balance between the spiritual and social needs of the community, while also strengthening communication, mutual cooperation, and a sense of togetherness. Thus, the routine Yasinan and Tahlilan activities in Dukuh Dayakan have proven capable of fostering a sustainable culture of harmony. The continuity of this tradition needs to be preserved and passed down to the next generation as an important pillar in preserving religious values, social solidarity, and local cultural identity amidst the current of modernization.